2021
DOI: 10.3390/cancers14010136
|View full text |Cite
|
Sign up to set email alerts
|

A Gene Signature Derived from the Loss of CDKN1A (p21) Is Associated with CMS4 Colorectal Cancer

Abstract: The epithelial–mesenchymal transition (EMT) is associated with tumor aggressiveness and increased invasion, migration, metastasis, angiogenesis, and drug resistance. Although the HCT116 p21-/- cell line is well known for its EMT-associated phenotype, with high Vimentin and low E-cadherin protein levels, the gene signature of this rather intermediate EMT-like cell line has not been determined so far. In this work, we present a robust molecular and bioinformatics analysis, to reveal the associated gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Guinney et al previously found different associations between CMS groups and clinical variables, including overall survival (OS) [3]. Although subsequent publications show controversial data regarding the OS between different CMS, in a recent study, we highlighted the differences in prognosis observed between CMSs (taking into account gene expression signatures), confirming the clinical relevance of the biological processes implicated in each CMS [34,35]. In light of this, we aimed to investigate the potential impact of CBLL1 as a prognostic marker (measuring OS).…”
Section: Analysis Of Survival Of Crc Samples Classified In Cms2supporting
confidence: 72%
“…Guinney et al previously found different associations between CMS groups and clinical variables, including overall survival (OS) [3]. Although subsequent publications show controversial data regarding the OS between different CMS, in a recent study, we highlighted the differences in prognosis observed between CMSs (taking into account gene expression signatures), confirming the clinical relevance of the biological processes implicated in each CMS [34,35]. In light of this, we aimed to investigate the potential impact of CBLL1 as a prognostic marker (measuring OS).…”
Section: Analysis Of Survival Of Crc Samples Classified In Cms2supporting
confidence: 72%
“…The p21-ZEB1 complex inhibits EMT in cultured cells. 28 The gene signature from the colon cancer tissues of p21 loss is associated with Consensus Molecular Subgroup 4 (CMS4), 29 which is characterized by wound response and EMT. 1 These results suggest the p16-high/p21-low cells in the EMT state.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-149-3p, a microRNA highly expressed in ovarian cancer patients, promotes EMT, in part by downregulating CDKN1A/p21 expression at both the RNA and protein levels [117]. In addition, loss of CDKN1A/p21 is associated with CMS4 colorectal cancer, an aggressive form of colorectal cancer characterised by the presence of mesenchymal-type cells [118].…”
Section: Cdkn1a/p21 Activation or Repression During Emt Invasion And ...mentioning
confidence: 99%